The Design of Smart Coffee Drying Technology Innovation Based on Ultrasonic Chill to Achieve Inclusive and Sustainable Agro-Industry in the New Normal (Journal of Advances in Information Systems and Technology, 2020)
Drying coffee beans manually using sunlight has disadvantages. When the weather suddenly changes, it will be difficult for coffee farmers to move coffee beans to a place that is protected from the rain. If allowed to rain, the slightly dry coffee beans will become wet and damp again. Humid conditions of coffee beans will reduce their quality. Coffee beans that return to wetness also cause longer drying time, disrupting the supply chain. This study aimed to determine the potential of COSMON as a smart drying technology based on ultrasonic chill. This research uses literature study, which is continued with tools, programs, mechanics; tools testing; and results analysis. This study results that the mass decrease is proportional to the rapid decline in air content. The fastest reduction rate was obtained from vacuum chill drying with the frequency of 45000 Hz because the higher the frequency value, the higher the ultrasonic frequency waves absorbed by the specimen. The more ultrasonic wave vibrations absorbed by the specimen, the faster the drying rate will occur. As a result, the coffee's average dry weight is 84% of its initial weight.